Capsulotomy for Treatment of Compartment Syndrome in Patients with Post Extracorporeal Shock Wave Lithotripsy Renal Hematomas: Safe and Effective, But Also Advisable? - Ghazal, Andreas Al; Schnoeller, Thomas J.; Baechle, Christian; Steinestel, Julie; Jentzmik, Florian; Steffens, Sandra; Hirning, Christian; Schrader, Mark; Schrader, Andres J. (Urology Journal, 2014)
<!--[if gte mso 9]> 0 0 1 240 1517 z 12 3 1754 14.0 96 800x600 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false DE JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Normale Tabelle"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Calibri;} --> <!--[endif] --> <!--StartFragment--> Abstract Purpose: To examine whether surgical decompression of hematomas by capsulotomy can help to improve long-term renal function following extracorporeal shock wave lithotripsy (SWL). Materials and Methods: This study retrospectively identified 7 patients who underwent capsulotomy for post SWL renal hematomas between 2008 and 2012. The control group comprised 8 conservatively treated patients. The median follow-up time was 22 months. Results: The two groups were comparable in age, gender, body mass index, risk factors for developing hematomas (renal failure, urinary flow impairment, indwelling ureteral stent and diabetes mellitus) and the selected SWL modalities. Hematoma size was also similar. However, significantly more patients in the surgical group had purely intracapsular hematomas (85.7% vs. 37.5%) without a potentially pressure-relieving capsular rupture. There were no significant differences in the post-interventional drop in hemoglobin, rise in retention parameters or drop in glomerular filtration rate (GFR). No capsulotomy-related complications were observed, but surgery required a significantly longer hospital stay than conservative management (median, 9 days vs. 5 days). The two groups also showed comparable recovery of renal function at long-term follow-up (median change in GFR from baseline, 97.1% and 97.8%, respectively). Conclusion: Since renal function did not differ between the two treatment groups, the conservative management remains the standard treatment for post-SWL renal hematoma. <!--EndFragment-->